2022
DOI: 10.1007/s10456-022-09860-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and vascular remodeling in COVID-19 hearts

Abstract: A wide range of cardiac symptoms have been observed in COVID-19 patients, often significantly influencing the clinical outcome. While the pathophysiology of pulmonary COVID-19 manifestation has been substantially unraveled, the underlying pathomechanisms of cardiac involvement in COVID-19 are largely unknown. In this multicentre study, we performed a comprehensive analysis of heart samples from 24 autopsies with confirmed SARS-CoV-2 infection and compared them to samples of age-matched Influenza H1N1 A (n = 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Both clinical studies and autopsy findings have also shown vascular damage and thrombotic complications in different organs, as seen in myocardial, liver, kidney, and intestinal injury [ 4 , 12 ]. Increasing clinical evidence suggests a key role of ECs in triggering and sustaining these phenomena by promoting inflammatory, angiogenic, and clotting cascades [ 40 , 41 , 42 ]. Initial dysfunction of the endothelial barrier and vascular leakage have also been considered responsible for an indirect immune-mediated mechanism of endothelial injury [ 12 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical studies and autopsy findings have also shown vascular damage and thrombotic complications in different organs, as seen in myocardial, liver, kidney, and intestinal injury [ 4 , 12 ]. Increasing clinical evidence suggests a key role of ECs in triggering and sustaining these phenomena by promoting inflammatory, angiogenic, and clotting cascades [ 40 , 41 , 42 ]. Initial dysfunction of the endothelial barrier and vascular leakage have also been considered responsible for an indirect immune-mediated mechanism of endothelial injury [ 12 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… 141 , 142 This type of angiogenesis is characterized by blood vessels splitting into two lumens after forming an intraluminal septum (inside to outside growing) mainly due to microthrombi presence, and it was reported to be macrophage-dependent in COVID-19 patients. 143 , 144 In fact, enhanced circulating levels of VEGF were observed in COVID-19 patients and even correlated with disease severity. 145 Intussusceptive angiogenesis may contribute to COVID-19 abnormalities as it disturbs the regular blood flow, leading to further microthrombi formation.…”
Section: Changes In Blood Vessel Permeability Due To Coronaviruses An...mentioning
confidence: 99%
“… 59 Histopathology from 24 confirmed SARS-CoV-2 cardiac autopsy samples compared with 16 age-matched influenza H1N1 A cardiac samples, 8 lymphocytic noninfluenza myocarditis, and 9 noninflamed heart tissues revealed that viral myocarditis was not evident in the SARs-CoV-2 samples; rather, there was a significant increase in perivascular CD11b/TIE2+ macrophages, a finding not seen in the 3 comparison groups, suggesting that cardiac involvement in SARS-CoV-2 may be predicated upon a macrophage-driven inflammatory process. 60 Additional studies suggest that the inflammatory response in acute SARS-CoV-2 infection provokes AutoAb (autoantibody) production targeting cardiac antigens. In one study of 104 patients hospitalized with COVID-19, 68% (71) had anticardiac autoAbs: 39% had anticardiac IgG autoAbs, 51% had anticardiac IgM autoAbs, and 22% had both.…”
Section: Pathogenic Theories In Pascmentioning
confidence: 99%